2011
DOI: 10.7150/ijms.8.106
|View full text |Cite
|
Sign up to set email alerts
|

Segment-orientated analysis of two-dimensional strain and strain rate as assessed by velocity vector imaging in patients with acute myocardial infarction

Abstract: Aims: Strain rate imaging techniques have been proposed for the detection of ischemic or viable myocardium in coronary artery disease, which is still a challenge in clinical cardiology. This retrospective comparative study analyzed regional left ventricular function and scaring with two-dimensional strain (2DS) in the first 4 to 10 days after acute anterior myocardial infarction (AMI).Methods and results: The study population consisted of 32 AMI patients with an LAD occlusion and successful reperfusion. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Although the research indicated that two‐dimensional echocardiography‐derived deformation analysis allows use of a form of myocardial function analysis which was more sensitive, the ability to detect myocardial viability was not hinted. Butz et al 14 have shown that 2D strain imaging has been proposed for the detection of ischemic or viable myocardium in CAD. In their study, they focused on the longitudinal velocities and deformation markers because ischemia especially affects subendocardial fibers first, which are mainly responsible for longitudinal movement 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the research indicated that two‐dimensional echocardiography‐derived deformation analysis allows use of a form of myocardial function analysis which was more sensitive, the ability to detect myocardial viability was not hinted. Butz et al 14 have shown that 2D strain imaging has been proposed for the detection of ischemic or viable myocardium in CAD. In their study, they focused on the longitudinal velocities and deformation markers because ischemia especially affects subendocardial fibers first, which are mainly responsible for longitudinal movement 15 .…”
Section: Discussionmentioning
confidence: 99%
“…VVI is a method used to quantify myocardial wall motion through the combination of speckle tracking, tissue‐blood border detection, and myocardial shape (28). It is an angle‐independent measurement technique, which has been extensively used to investigate LV strain and twist in health and disease (19,29,30,31) and validated against sonomicrometry (28) and magnetic resonance imaging (32). VVI provides sensitive indexes of myocardial relaxation and contractility relatively independent of loading conditions and is able to detect early functional abnormalities (15,16,17,18).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Offline post-processing analysis was performed using the VVI software package (Siemens Medical, Malvern, PA, USA). Velocity Vector Imaging uses a series of unique B-mode pixel-tracking algorithms whose details and methodology are described in the manufacturer's patent US 6,909,914 and patent application publications US 2005/0070798 and US 2005/007415314 [3,4,22].…”
Section: Echocardiographymentioning
confidence: 99%